Clinical follow-up does not improve survival after resection of stage I–III colorectal cancer: A cohort study. (May 2015) - Jones, R.P.; McWhirter, D.; Fretwell, V.L.; McAvoy, A.; Hardman, J.G.
Abstract: Introduction: The benefit of clinical follow-up alongside CT & CEA in detecting recurrent colorectal cancer (CRC) remains unclear. Despite this, clinical review remains part of most surveillance protocols. This study assessed the efficacy of clinical follow-up in addition to CT/CEA in detecting disease recurrence. Methods: Patients undergoing surgery for CRC at a single centre between 2009 and 2011 were identified. Follow-up included clinical review, CT and CEA for 5 years. The primary endpoint of the study was method of detection of recurrence. Secondary endpoints included detection of surgically treatable recurrence, compliance with follow-up, disease free survival and overall survival. Results: 118 patients with stage I–III CRC were included. Only 68.9% of scheduled follow-up events were performed (76.6% clinical reviews, 76.2% CT scans and 60.4% CEA tests). At median follow-up of 36 months, 26 patients had developed recurrence (median DFS 45.8 months). 17 patients (14.7%) had died (median OS 49.3 months). Sensitivity and specificity of follow up modality in detecting recurrence were; CT (92.3%, 100%), CEA (57.7%, 100%), clinical review (23.0%, 27.2%). Addition of clinical review did not identify any disease recurrence that was not detected by scheduled CT. Eight patients (30.7%) had surgically treatable recurrence – all were identified by scheduled CT. Conclusion: The addition of CEA testing and clinical review to scheduled CT scanning offered no benefit in the detection of recurrent disease. Clinical review could be removed from follow-up protocols without any reduction in the detection of recurrent cancer. Highlights: We investigated follow up after surgery for colorectal cancer. The benefit of clinical review in addition to CT scanning is unclear. We compared CT scans, CEA and clinical review for detecting recurrent cancer. One third of recurrences were treatable by repeat surgery. Clinical review did not detect any additional recurrences.